Quantitative Analysis of Potamogeton Crispus in Dongping Lake Based on Remote Sensing - WU Chunhui; LIU Shufen; SANG Yanyan; ZHANG Qiuying; LI Fadong; LI Zhaoxin; XIAO Jieying (Renmin Zhujiang)
Under the background of rapid urbanization,rapid economic development and industrialization level improvement,the lake water quality is deteriorating,with increasingly serious eutrophication.So it is of great significance to strengthen the monitoring and control of lake water quality.Taking Dongping Lake as the research object,this paper quantitatively analyzes the dynamic change of Potamogeton crispus in Dongping Lake by remote sensing method,with purpose to reveal the seasonal biomass dynamics of Potamogeton crispus in Dongping Lake,clarify its impact on the total phosphorus of Dongping Lake,and provide scientific support for water quality control,especially total phosphorus control.The results show that:The vegetation in the lake water in 2018 was less than that in 2017 by visual interpretation,and showed a decline trend in concentric way from the center of the lake,which indicated that the local government and environmental protection departments has spared no efforts in governance;The dry matters in 2018 were less than those in 2017.It is a great contribution to total phosphorus of lake water by the death of Potamogeton crispus.